Kojenerasyon Ve Güneş Enerjisinin Bütünleştirildiği Hibrit Sistemin Ekonomik Ve Emisyon Analizi - Özkoca, Meryem İpek (Enerji Enstitüsü, 2019)
Nüfus artışı ve ekonomik büyümeyle birlikte gelen enerji talebinin karşılanmasının önemi gündemi daha fazla meşgul etmeye başlamıştır. Bunun yanında Paris Anlaşması gibi toplantıların ana konusu olan iklim değişikliği de enerji stratejilerinin gözden geçirilip geliştirilmesi zorunluluğunu ortaya çıkarmaktadır. Enerjinin güvenli ve sürdürülebilir olmasını sağlarken temiz enerji teknolojileri alanında ilerlemek de dünya ülkelerinin dikkate alması gereken konular arasında yer almaktadır. Yenilenebilir enerji kaynaklarının en önemli dezavantajlarından biri hava koşullarından doğrudan etkilenmeleridir. Enerjinin depolanması ile ilgili araştırmalar devam etmektedir. Şu an için var olan durumda üretilen enerjinin etkin bir şekilde depolanamıyor olduğunu düşünerek, yenilenebilir enerji kaynaklarından üretilen enerjinin o kaynağın varlığına doğrudan bağımlı olduğunu söylemek mümkündür. Enerji üretim sistemlerinin verimli bir şekilde tasarlanması ve hayata geçirilmesi, kaynağın en doğru şekilde kullanılmasını sağlarken enerji üretim maliyetlerini de azaltmaktadır. Akıllı şebekeler gibi konuların da konuşulmaya başlandığı bu günlerde enerji üretim sistemlerinin verimliliğine verilen önem de değer kazanmaya devam etmektedir. Hibrit enerji üretim sistemleri iki ya da daha fazla enerji kaynağının bir araya getirilerek kurulan sistemlerdir. Bu sistemlerle enerji üretiminin verimli bir şekilde gerçekleşmesi sağlanabilir. Fosil yakıtla birlikte yenilenebilir enerji kaynağının bir araya getirilmesiyle kurulan hibrit sistemlerle, hava koşullarına doğrudan bağımlı olan yenilenebilir enerji kaynağının eksikliğini fosil yakıt tamamlayabilmektedir. Hibrit enerji üretim sistemleriyle dengeli bir enerji arzı sağlanırken, aynı zamanda fosil yakıt kullanımı azaltılarak enerjide dışa bağımlılığın azaltılmasına katkı sağlanabilmektedir. Türkiye'nin cari açığının en büyük sebeplerinden biri enerjidir ve Türkiye enerjide büyük oranda dışa bağımlı bir ülkedir. Enerji üretiminde yerli ve yenilenebilir enerji kaynaklarının kullanım oranın arttırılması ile fosil yakıtlara olan bağımlılık azaltılabilecektir. Hibrit enerji üretim sistemleri de yenilenebilir enerji kaynaklarının kullanım oranını arttıran sistemlerdendir. Çalışmada Türkiye'de çok az uygulaması olan fosil+yenilenebilir enerji hibrit üretim sistemlerinin uygulanabilirliğinin gösterilmesi amaçlanmıştır. Bu amaç için Denizli'de 12 MW kurulu güce sahip olan bir kojenerasyon santralinden alınan verilerle birlikte HOMER simülasyon programı kullanılarak bir örnek durum incelenmiştir. Hibrit sistemde kullanılacak olan yenilenebilir enerji kaynağı, Denizli'de verimliliği yüksek olan güneş olarak seçilmiştir. Güneş+kojenerasyon hibrit üretim sistemi, var olan kojenerasyon sistemi ile ekonomik açıdan ve sera gazı emisyonlarına göre karşılaştırılmıştır. Çalışmada Senaryo 1 piyasada var olan elektrik ve doğal gaz fiyatlarıyla gerçekleştirilmiş olan simülasyondur. Duyarlılık analizi kapsamında Senaryo 2 ve Senaryo 3 olacak şekilde 2 farklı simülasyon daha incelenmiştir. Tüm senaryoların sonuçları birbirleri ile karşılaştırılmıştır. Simülasyon sonuçlarına göre, tüm senaryolarda hibrit sistemin net şimdiki maliyetinin kojenerasyon sisteminden daha az olduğu görülmüştür. Hibrit sistemler arasında en yüksek net şimdiki maliyet, 393.430.800 $ ile, var olan şebeke elektrik fiyatı ve doğal gaz fiyatının alındığı Senaryo 1 sonucunda çıkmıştır. İskontolu geri dönüş sürelerine bakıldığında, net şimdiki maliyeti 390.567.300 $ ile Senaryo 1'e yakın olmasına rağmen, hibrit sistemler arasında en düşük süre 7,77 yıl ile Senaryo 2 sonucunda çıkmıştır. Konvansiyonel sistem ile hibrit üretim sistemin sera gazı emisyonları açısından çevreye olan etkilerinin de incelendiği simülasyon sonuçlarına göre, yıllık toplam sera gazı emisyonlarında hibrit sistem kullanımıyla konvansiyonel sisteme göre azalma olduğu görülmüştür. Elektrik üretiminde yenilenebilir enerji kaynağı kullanımı sırasıyla %38,30 ve %17,40 olan Senaryo 1 ve Senaryo 3'ün sonuçlarına göre toplam emisyon miktarında yıllık sırasıyla %20 ve 23'lük bir azalma sağlanmıştır. Elektrik üretiminde yenilenebilir enerji kaynağı kullanım oranı %12,20 olan Senaryo 2 için ise toplam emisyon miktarında azalma oranı yıllık %14 'tür. Hibrit enerji üretim sistemlerinin Türkiye'de yaygınlaşması ile birlikte 2023 hedeflerine ulaşmaya katkı sağlanacağı, ülkenin büyümesine olumlu etkileri olacağı söylenebilir. Hibrit sistemler ile ilgili yapılan çalışmaların arttırılması ve ülkede uygulanabilirliğinin fazlalaştırılması için gerekli potansiyeli bulunmaktadır.

Historical and current energy production systems are dominated by fossil fuels such as coal, oil and gas. It is a wellknown fact that using fossil fuels in energy production system causes production of greenhouse gas emissions which are the main reason of climate change. Due to these environmental facts, it is going to be much more significant to balance development and environment in energy production systems. Also, alternative and clean energy sources continue to increase their importance in energy strategies. The importance of providing energy demand, which comes from population growth and booming economy, is being on the front more than ever. Also climate change, which is the main subject of congregations like Paris Agreement, is causing the review and development of energy strategies too. Like ensuring reliable and sustainable energy, progressment in clean energy technologies is also one of the issues that the governments must pay attention. Renewable energy sources can be said that they are alternative, clean and sustainable energy sources. In addition to that, using renewable energy sources means evaluating domestic sources and reducing the dependency on external energy. As in other energy production systems, renewable energy generation systems should be designed effectively and the resources should be used efficiently because of their disadvantages. One of the most important disadvantages of renewable energy resources is that they are affected directly from weather conditions. Considering the current situation, that produced amount of energy is not able to be stored effectively - the research and development studies are in progress - it is possible to claim that produced amount of renewable energy is dependent on its resource's existence directly. This creates challenges for power system operators when it comes to meeting and optimizing energy demand. Designing and building efficient power generation systems are helping the usage of resource correctly while it reduces the cost of power generation. Like smart grids, efficiency of power generation systems' precedency as subjects are being discussed nowadays. Hybrid energy systems are made of combination of two or more energy resources. Power generation could be more efficient by using hybrid energy systems. By the usage of hybrid energy systems, fossil fuels can make up the renewable energy systems' dependence on weather conditions. The use of renewable energy sources, primarily wind and solar, is expected to grow significantly within Turkey's power system. With this expectation, it is needed to understand better how the increasing share of renewable energies, especially wind and solar will affect Turkey's power system. One way of increasing the installed capacity is building power plants on the areas with high measurement values. The other way is combining solar plants with existing fossil fuel power plants which are located on the ares with high solar radiation measurement values. Usage of hybrid energy production systems provides a balanced energy supply while it reduces the demand of fossil fuel and as a result, contributes to a lesser dependance on foreign energy. One of the greatest reasons of Turkey's current account deficit is energy and Turkey is foreign dependent on the subject of energy. Increase in local and renewable energy resources' usage would reduce the dependence on fossil fuel. Hybrid power generation systems are also increasing the ratio of renewable resources' usage. During the literature review, hybrid energy systems applications in the world were encountered. Hybrid energy production systems with renewable energy sources combined with fossil fuels have also been seen with only renewable energy hybrid systems. The study is aimed to show feasibilty of fossil & renewable hybrid energy systems, which are used narrowly in Turkey. For this purpose, a model has been simulated using HOMER simulation program and the data gathered from a cogeneration power plant which has a 12 MW installed power in Denizli. Renewable energy resource is chosen as solar energy because it has a high capacity in Denizli. Solar & Cogeneration hybrid power system has been compared with the existing cogeneration system in terms of economy and envirionment. After entering seasonal electricity and thermal demand porfiles in the simulation program, solar radiation and irradiance for Denizli are also entered. Hybrid cogeneration system which includes PV, gas turbine, grid, converter and boiler as a component is designed and the simülation results are gathered. Results are anlyzed by its economic and emisson results. Scenario 1 in the study is the simulation designed with the current electricity and natural gas prices. As sensitivity analysis, two more simulations -Scenario 2 and Scenario 3- were studied. Outputs of all three scenarios were compared with each other. According to the results of these simulations, it has been seen that net present cost of hybrid system is lower than cogeneration system in all scenarios. The highest net present cost among hybrid systems is Scenario 1 as $393,430,800 where grid electric price and natural gas price are current prices. Considering discounted payback periods of these studies, minimum payback period belongs to Senario 2 with 7.77 years despite its $ 390,567,300 net present cost which is close to the highest cost of Scenario 1. In all three scenarios, conventional system and hybrid system have also been analyzed in terms od green house gas emissions. Accordingly, green house gas emissions by hybrid system are less than emissions of conventional system. Based on the data of Scenario 1 and Scenario 3, where renewable energy resources' rates are 38.30% and 17.40% respectively, a decrease in annual greenhouse gas emmisions have been calculated as 20% and 23%. Decreasing of green gas emissions in scenario 3 is 14% where renewable energy resource rate in electricity production is 12.20%. Due to the affordable technology costs, it is expected that the investment appetite for solar energy will be higher. Turkey has its own potential to increase its solar installed power. Beside the fact that, using renewable energy is better for the environment, assessing the pottential of solar energy will contribute to Turkey's economy too. It could be claimed that expanding of hybrid energy systems in Turkey could help the achievemnt of 2023 goals and growth of economy. Turkey has the necessary potential of increasing the number of researches about hybrid systems and feasibility augmentations within country. It can be noted that, in addition to economic gains, reducing the environmental pollution can be a reason to increase researches about renewable and fossil fuels hybrid energy production systems and develop these systems in Turkey.
Economic And Emission Analysis Of Hybrid Cogeneration System Integrated With Solar Energy
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Enerji Enstitüsü, 2019
Thesis (M.Sc.) -- İstanbul Technical University, Energy Institute, 2019
Keywords: Güneş enerjisi; Solar energy